Evaluation Of Policy Implementation Of Discipline And Law Enforcement Of Corona Virus Disease Health Protocol (Covid-19) Year 2020 - Agus Supriyadi; Nandang Alamsah Delianoor; Heru Nurasa; Ramadhan Pancasilawan (Aliansi, 2022)
The Corona Virus Disease 2019 (covid-19) pandemic came suddenly and changed many aspects of policy around the world. The central and local governments immediately responded to this by making policies that could reduce the spread and ensure that the community could carry out activities by implementing health protocols. Then the Banten Provincial government responded by issuing Banten Governor Regulation Number 45 concerning Amendments to Banten Governor Regulation Number 38 of 2020 Implementation of Discipline and Law Enforcement of Health Protocols as an Efforts to Prevent and Control Covid-19. Then, the policy of applying discipline and law enforcement in handling Covid-19 Banten Province faces obstacles in carrying out its duties. This article will discuss the evaluation of the policy of implementing discipline and law enforcement of the Covid-19 health protocol in Banten Province in 2020. This research uses a descriptive qualitative approach. In collecting data, this research uses observation, interviews, literature study, and internet searching. Data collection in this study was carried out by studying the existing literature. In this study, the evaluation theory proposed by William N Dunn consists of 6 indicators related to program evaluation, namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. The findings of this study are the need for an evaluation of this policy, especially regarding the need to improve regulations into regional regulations which were previously only governor regulations so that they can become legal products that can contain strong and binding sanctions.